Monitoring Free‐Living Honeybee Colonies in Germany: Insights Into Habitat Preferences, Survival Rates, and Citizen Science Reliability - Benjamin Rutschmann; Felix Remter; Sebastian Roth (Ecology and Evolution, 2025)
ABSTRACT Our understanding of the western honeybee (Apis mellifera) predominantly stems from studies conducted within beekeeping environments, leaving the presence and characteristics of honeybees outside managed settings largely unexplored. In this study, we examined the habitats, nesting sites, and survival rates of free‐living colonies through personal monitoring of nest sites in Munich (N = 107) and the coordination of Citizen Science monitoring across Germany (N = 423). Within 7 years, we collected 2555 observations on 530 nest sites from 311 participants, including the authors. Overall, we found that 31% of the occupied nest sites were in buildings and 63% in mature trees, with clear preferences for specific tree species. Nesting preferences differed between urban, rural, and forested areas. On average, only 12% of the personally monitored colonies in Munich survived annually, a figure that aligns well with other published studies in Germany but contrasts sharply with the significantly higher survival rates resulting from Citizen Science reports (29%)—a discrepancy likely driven by certain reporting biases. We found that Citizen Science yielded significantly fewer updates per colony, underreported abandoned sites, and that 46% of overwintering reports overlapped with the swarming season and had to be excluded. To gain reliable survival data in Citizen Science projects, consistency and timing of reports need particular attention and regional swarming should be monitored as well. This study enhances our understanding of the ecological dynamics, liminal state, and conservation needs of free‐living honeybee cohorts, addresses potential Citizen Science monitoring biases, and suggests standardized data collection protocols for future monitoring projects. The preservation of mature trees with suitable cavities, as well as the provision of additional nesting sites, is key for sustaining free‐living honeybee cohorts and should be integrated into conservation strategies, urban planning, and forest management.